The Concept of Inclusive Economy as a Component of Sustainable Development - Krysovatyy, Andriy; Ptashchenko, Olena; Kurtsev, Oleksii; Ovagim, Arutyunyan (Problemy Ekorozwoju, 2024)
This research is based on the current issue of the lack of inclusivity in the economy as a hindrance to sustainable development. Governments, organizations, and individuals are considering the issues of inclusive economy on a practical level in the form of programs, strategies, or regulatory documents. The study and consideration of socio-economic processes were conducted through the analysis of scientific activity and its results, providing insights into current interests, problems, and needs of society in conditions of sustainable development. The methodological basis of the research includes general philosophical and general scientific methods. The purpose of this study is cognitive modeling of the concept of inclusive economy as a component of sustainable development. The authors argue and justify that inclusive economy is a crucial component of sustainable development. To achieve the goal of the study, the authors identified four key blocks on which the concept of inclusive economy is built in the context of sustainable development: terminological (defining key terms), fundamental (establishing underlying principles), substantive (identifying specific elements), and applied (practical applications). The concept of an inclusive economy is based on the principle of providing all members of society with free and equal access to resources and results of economic activity, which is essential for achieving sustainable development goals. The paper presents data from the index of inclusive development, which assesses the performance of developing countries in achieving inclusive growth and development. The index takes into account environmental and social issues, which underscores the need for developing an inclusive economy as a crucial component of sustainable development. The proposed concept of an inclusive economy as a component of sustainable development will ensure the appropriate level of inclusive economic growth and development by promoting equity, social inclusion, and environmental sustainability.